Assess the Level of Smooth and Stable of the Suspension when Convert from Mechanical Suspension to Air Suspension - Huy Nguyen Huu; Thoi Le Nam; Lanh Le Thanh (International Journal of Research in Vocational Studies (IJRVOCAS), 2022)
This report illustrates the result of the calculation of the level of smoothness and stability of the bus when converting suspension from mechanical suspension to air suspension. The mechanical vibrations of the automobile in the moving process include amplitude, frequency, and acceleration. These factors may affect the safety of goods and the human state on the bus. This result also shows the great strengths of air suspension over mechanical suspension so that the requirement of a smooth level of movement is guaranteed which is a good condition to rise the safety of goods in the bus, maintain human health, and reduce physical fatigue and psychological tiredness of drivers and passengers.